Global environmental impacts of food system from regional shock: Russia-Ukraine war as an example - Haoran Zhang; Limin Jiao; Cai Li; Zhongci Deng; Zhen Wang; Qiqi Jia; Xihong Lian; Yaolin Liu; Yuanchao Hu (Humanities & Social Sciences Communications, 2024)
Abstract Different responses to external interference, such as regional conflict, could have distinct sustainability outcomes. Here, we developed a novel framework to examine global food shortages from the Russia-Ukraine conflict and quantify the embodied environmental impacts of disturbed and alternative food supply chains. The conflict could soon bring a 50–120 Mt shortage of nine dominant food products and cause temporal global cropland abandonment and greenhouse gas emissions decline. By contrast, the partial agricultural recovery in the next cultivation season will raise global cropland use and greenhouse gas emissions by 9–10% and 2–4% (mainly in China and Europe). However, optimized food supply networks with prioritized agricultural expansion in higher-efficiency countries could minimize food shortages and food-mile expenses, offsetting the postwar environmental increments from agricultural recovery by 45–89%. These results validate a framework to simulate the global social-ecological system, and underline the resistance opportunities and tele-connected consequences of regional disturbance.